Science Learning Innovation Through STEM-Based LKPD to Improve Science Literacy in the Industrial Revolution 4.0 Era - Tihasanah, Tihasanah; Saminan*, Saminan; Evendi, Evendi; Afdzaluddin, Atiqah Mohd (Universitas Syiah Kuala, 2025)
The development of technology in the industrial revolution 4.0 era demands an increase in the quality of science education, especially in developing students' scientific literacy. This study aims to develop student worksheets (LKPD) based on science, technology, engineering, and mathematics (STEM) to improve students' scientific literacy in physics learning. The research method uses research and development with the analysis, design, development, implementation, evaluation (ADDIE) model. The subjects of the study were students of class XI IPA SMAN 4 Kota Langsa in the 2024/2025 academic year. The research instruments included material and media expert validation sheets, student response questionnaires, and science literacy tests. The results showed that the STEM-based LKPD developed was valid with a material expert validation score of 4.2 (very valid) and a media expert of 4.3 (very valid). The implementation of STEM-based LKPD increased students' scientific literacy with an N-gain of 0.73 (high). Student responses to LKPD showed a very positive category with a percentage of 82.6%. Based on the research results, STEM-based LKPD has proven effective in integrating science concepts with technology, engineering, and mathematics applications that are relevant to the needs of the 21st century